Development of Rhamnolipid Based White board cleaner - Turbekar, Reshma; Malik, Nagesh; Dey, Debarshi; Thakare, Deepak (International Journal of Applied Sciences and Biotechnology, 2014)
In the present study biosurfactant based white board cleaner was formulated, using column purified rhamnolipid produced by Pseudomonas aeruginosa. A rhamnolipid concentration of 0.01% was finalized, as it was efficiently able to remove fresh and aged white board marker stains on white board. The rhamnolipid formulation was found to be stable over a tested span of 6 months and it did not exhibit any cytotoxicity on Human Lung Epithelial Cell Line (L132) and Normal Human Skin Fibroblast (NHSF) cell line. The cleaning efficiency was equivalent to conventional synthetic surfactants, but the biosurfactant based approach is more environment friendly and biocompatible. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11589 Int J Appl Sci Biotechnol, Vol. 2(4): 570-573